Plasmodesmata mediate cell-to-cell transport of brassinosteroid hormones - Wang, Yaowei; Perez-Sancho, Jessica; Platre, Matthieu Pierre; Callebaut, Brenda; Smokvarska, Marija; Ferrer, Karoll; Luo, Yongming; Nolan, Trevor M; Sato, Takeo; Busch, Wolfgang; Benfey, Philip N; Kvasnica, Miroslav; et al. (Nature chemical biology, 2023)
Brassinosteroids (BRs) are steroidal phytohormones that are essential for plant growth, development and adaptation to environmental stresses. BRs act in a dose-dependent manner and do not travel over long distances; hence, BR homeostasis maintenance is critical for their function. Biosynthesis of bioactive BRs relies on the cell-to-cell movement of hormone precursors. However, the mechanism of the short-distance BR transport is unknown, and its contribution to the control of endogenous BR levels remains unexplored. Here we demonstrate that plasmodesmata (PD) mediate the passage of BRs between neighboring cells. Intracellular BR content, in turn, is capable of modulating PD permeability to optimize its own mobility, thereby manipulating BR biosynthesis and signaling. Our work uncovers a thus far unknown mode of steroid transport in eukaryotes and exposes an additional layer of BR homeostasis regulation in plants.
Keywords: Brassinosteroids; Hormones; rostliny; Plants; plazmodesmy; Arabidopsis Proteins; regulátory růstu rostlin; hormony; Plant Growth Regulators; Plasmodesmata; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; brassinosteroidy; proteiny huseníčku